Business Improvement Strategy and Benefit Cost Ratio of Bogares Peanut SMEs in Tegal Regency - Kusuma Putri, Septi; Dian Wisika Prajanti, Sucihatiningsih; Rusdarti, Rusdarti (Universitas Negeri Semarang, 2020)
SMEs (Small and Medium Enterprises) are small business activities carried out by someone, which need to be protected to prevent unfair business competition. Bogares peanuts are one of many businesses in the Tegal Regency which needs to be developed because Bogares peanut is one of the special snacks from Tegal Regency. The purpose of this study was to analyze internal and external factors, to analyze business improvement strategies and to analyze the costs and benefits of production in Bogares Peanut SMEs. The research method used in this study was the Mix Methods. The analysis was done by the researchers using the SWOT analysis to measure business conditions in stable or unstable conditions, and the Cost Benefit Analysis was done to determine whether or not the business was feasible to be developed. The population in this study were all Bogares peanuts SMEs in Tegal Regency. The sampling technique used saturated sampling technique and the data collection techniques was done through interviews, questionnaires, and documentation. The results showed the internal factors of Bogares Peanut SMEs consisting of seven strengths and three weaknesses, in addition based on the Internal Factor Evaluation (IFE) matrix analysis, as big as 2.621 was located in quadrant II which means Bogares Peanut SMEs in Tegal Regency were in stable condition; while external factors consisted of four opportunities and four threats, based on the analysis of the External Factor Evaluation (EFE) matrix as big as 2.407 lies in quadrant V, which means that Bogares Peanut SMEs were in a stable condition; the analysis of cost benefit obtained a total value of 1.69> 1 it showed that the Bogares Peanut SMEs deserve to be developed.